Unlock complex and streaming data with declarative data pipelines : how new technologies have transformed the way modern data is processed for analytics - Rafael, Ori; Hasson, Roy; Bilodeau, Rick (O'Reilly Media, Inc., 2022)
Unlocking the value of modern data is critical for data-driven companies. This report provides a concise, practical guide to building a data architecture that efficiently delivers big, complex, and streaming data to both internal users and customers. Authors Ori Rafael, Roy Hasson, and Rick Bilodeau from Upsolver examine how modern data pipelines can improve business outcomes. Tech leaders and data engineers will explore the role these pipelines play in the data architecture and learn how to intelligently consider tradeoffs between different data architecture patterns and data pipeline development approaches.